Intricacies of Using Spaced Repetition Tools - Ahmed Ghani (University Library System, University of Pittsburgh, 2024)
I was really intrigued to read an article by Cooper et al. that described how using spaced repetition study techniques raised GPA, USMLE Step 1, and COMLEX Level 1 results. In addition, I appreciate the writers' efforts in spreading the word about this special study technique that has been shown to improve grades. I do want to draw attention to a few areas of concern with this approach including the proper usage of the software as well as certain things that could have affected and altered the results of the study.